Discussion about math, puzzles, games and fun.   Useful symbols: ÷ × ½ √ ∞ ≠ ≤ ≥ ≈ ⇒ ± ∈ Δ θ ∴ ∑ ∫ • π ƒ -¹ ² ³ °

You are not logged in.

Matilde
Guest

Hi there!

(e^x sinx)^2

## #2 2005-10-31 03:40:39

mathsyperson
Moderator

Offline

### Re: Mathhelp!

Help how? You've just typed an expression involving rather complicated algebra and it is now just sitting there looking confused and asking for its mummy. What exactly do you want done to it?

Why did the vector cross the road?
It wanted to be normal.

Matilde
Guest

(e^x sinx)^2= ?

## #4 2005-10-31 04:24:46

kylekatarn
Power Member

Offline

### Re: Mathhelp!

(e^x sinx)^2 = (e^(2x)).(sinx)^2

## #5 2005-10-31 04:31:40

mathsyperson
Moderator

Offline

### Re: Mathhelp!

I agree. Unless there's a trigonometric identity that I am not aware of, that's the furthest it can be simplified.

Why did the vector cross the road?
It wanted to be normal.

## #6 2005-10-31 06:01:29

Matilde
Novice

Offline

### Re: Mathhelp!

Thanx kylekatarn!

I have to solve:

Volume=   ∫ π (e^2x * (sinx)^2 * dx ,0 ,π

I know that the integral of e^2x = 1/2 e^2x.... but I don't know what to do with (sinx)^2?

## #7 2005-10-31 08:21:48

Flowers4Carlos
Full Member

Offline

### Re: Mathhelp!

hi yaz matilde!!

oh geeez.... this is a tuff one!!  i will still give it a try!!!

∫e^(2x)sin²xdx                            sin²x = 1/2(1 - cos2x)

∫e^(2x)[1/2(1 - cos2x)]dx            let u=2x so du=2dx

1/2∫e^(u)[1/2(1 - cosu)]du

1/4∫e^(u)(1 - cosu)du

1/4∫e^(u)du - 1/4∫e^(u)cosudu

-1/4(∫e^(u)cosudu - ∫e^(u)du)                use integration by parts on ∫e^(u)cosudu
f(u) = e^(u)          g'(u) = cosu
f'(u) = e^(u)         g(u) = sinu
∫f(u)g'(u)du = f(u)g(u) - ∫g(u)f'(u)du

-1/4[(e^(u)sinu - ∫e^(u)sinudu) - ∫e^(u)du]     use integration by parts on ∫e^(u)sinudu
f(u) = e^(u)             g'(u) = sinu
f'(u) = e^(u)            g(u) = -cosu

-1/4[{e^(u)sinu - (-e^(u)cosu + ∫e^(u)cosudu)} - ∫e^(u)du]

-1/4[(e^(u)sinu + e^(u)cosu - ∫e^(u)cosudu) - ∫e^(u)du]

observe that ∫e^(u)cosudu = e^(u)sinu + e^(u)cosu - ∫e^(u)cosudu so

∫e^(u)cosudu + ∫e^(u)cosudu = e^(u)sinu + e^(u)cosu
2∫e^(u)cosudu = e^(u)sinu + e^(u)cosu
∫e^(u)cosudu = 1/2(e^(u)sinu + e^(u)cosu)

finally...

-1/4{[1/2(e^(u)sinu + e^(u)cosu)] - e^(u)}

you can plug u=2x back in there if ya want.  i may have done it all wrong or there may be an easier way of doing it   who knowns???

## #8 2005-11-07 21:58:59

Matilde
Novice

Offline

### Re: Mathhelp!

I know I’m late.. but… ThankYouVeryMuch!